THE EFFECT OF CAPITAL STRUCTURE, LIQUIDITY, PROFITABILITY, ACTIVITY, AND INSTITUTIONAL OWNERSHIP ON COMPANY VALUE AMONG MANUFACTURING COMPANIES LISTED ON INDONESIA STOCK EXCHANGE DURING 2017-2022 - Tania, Christina; Susanti, Merry (International Journal of Application on Economics and Business, 2023)
The value of a company that go public reflects the market price of the company's stocks. With the development of the company for the better, it will certainly affect the value of the company which will also increase. This study aimed at determining the effect of Debt to Equity Ratio (DER), Current Ratio (CR), Return on Equity (ROE), Total Assets Turnover (TATO), and Institutional Ownership (INST) on the Value of Manufacturing Companies listed in Indonesia Stock Exchange for the period 2017-2020. The sampling technique in this study used purposive sampling so that 56 companies were obtained. The research analysis method used was Panel Data Regression. The results showed that DER had a positive and significant effect on firm value, while CR, ROE, TATO, and INST had no influence on firm value.